Quality of radiology training and role of Royal Australian and New Zealand College of Radiology in supporting radiology trainees in NSW: Results of the first radiology trainee survey. Issue 3 (23rd February 2021) - Kyaw, Merribel M; Dedova, Irina; Young, Noel; Moscova, Michelle
Abstract: Introduction: The Royal Australian and New Zealand College radiology training programme is a 5‐year programme with a vast curriculum including reporting and research requirements. Undertaking training can be stressful for trainees who must balance their educational needs and work responsibilities. We undertook the first independent survey of New South Wales (NSW) radiology trainees to evaluate their perceptions about the quality of their training. Methods: Focus groups with trainees from multiple NSW training sites were conducted to construct a survey which was then distributed to all NSW Radiology trainees ( n = 118). Data from the survey were analysed, and factors correlating to the overall satisfaction with the programme were explored using Spearman's correlation. Results: Survey response rate was 70.3%. Eighty‐nine per cent of trainees were satisfied with their career choice, and 73% were satisfied with the training programme. Majority felt they had a good exposure to cases, modalities and access to resources to complete their training. Trainee satisfaction significantly correlated with a supportive work environment ( r s = 0.83, P < 0.0001), which involved supportive consultants ( r s = 0.75, P < 0.0001), good peer support ( r s = 0.60, P < 0.0001) and their training site respecting work/life balance ( r s = 0.62, P < 0.0001). As trainees progressed through the training programme, they became less satisfied, with trainees in years 3 and above being the most dissatisfied. Conclusion: NSW radiology trainees are generally satisfied with their training programme and career choices. Trainee satisfaction correlated most strongly with supportive work environment, good consultant support, peer relationships and good work/life balance; satisfaction decreased for senior trainees.